Style of Language in Tourism Hotel Advertising - Ni Putu Isha Aprinica (Linguistic, English Education and Art (LEEA) Journal, 2021)
This study aims to determine the style of language used in tourism hotel advertisements for promoting their hotels. The method used in this study taking samples from tourism hotel advertisements contained in the 2019 edition of the Bali Travel News newspaper and analyze them by the style language they used. The results showed that the language style that appears and is often used by the hotel to attract readers to stay at the hotel are hyperbole, metonymy, personification, and polysemy styles. In conclusion, the use of language style is one of the main factors when making advertisements, changing the meaning and use of figurative language to make sentences more beautiful to read. Keywords: Discourse, Hotel advertising, Language Style